EDUKASI MASYARAKAT DAN PELESTARIAN PENINGGALAN SEJARAH DI DESA REMBITAN KECAMATAN PUJUT KABUPATEN LOMBOK TENGAH - Muani, Muani; Afandi, Ahmad; Masyitah, Putri Maya; Mayasari, Dian Eka; Mubin, Ilmiawan; Zaenudin, Zainudin (Journal of Community Empowerment, 2023)
ABSTRAK                                                                                      Edukasi dan pelestarian peninggalan sejarah kepada mahasiswa pendidikan sejarah berkerjasama dengan masyarakata setempat mengenalkan tempat bersejarah dan mengadakan pembugaran makam Nyatok. Bertujuan untuk memberikan wawasan pengetahuan tetang peninggalan sejarah dan sosialisasi kepada masyarakat untuk melestarikan peninggalan bersejarah yang ada di Desa Rembitan. Metode yang digunakan adalah mengenalkan tempat peniggalan sejarah dan bergotong royong bersama masyarakat melestarikan peninggalan sejarah seperti, Cakar budaya Masjid Kuno Rembitan, Rumah asli suku sasak Dusun Sade dan Makam Wali Nyatoq. Hasil dari kegiatan edukasi dan pelestarian tempat peningalan sejarah bahwa mahasiswa antusias dalam mengikuti kegiatan edukasi dan pelestarian tempat peninggalan sejarah dan masyarakat juga antusias berkerjasama mengenalkan dan melestarikan tempat bersejarah di desa Rembitan.  Kata kunci: Edukasi Masyarakat; Peningalan Sejarah; Lombok Tengah. ABSTRACT The aim of this project is to educate history students on the importance of preserving historical heritage in collaboration with local communities. This includes introducing historical places and restoring the Nyatok tomb. The project seeks to provide insight into historical relics and promote socialization within the community to encourage of historical artifacts in Rembitan Village. The method used is to identify historical heritage sites and collaborate with the community to preserve them. Examples of such sites include the Rembitan Ancient Mosque, the traditional house of the Sasak tribe in Sade Hamlet, and the Tomb of Wali Nyatoq. The educational activities and preservation of historical heritage sites have resulted in enthusiastic participation from students and cooperationThe aim of this project is to educate history students on the importance of preserving historical heritage in collaboration with local communities. This includes introducing historical places and restoring the Nyatok tomb. The project seeks to provide insight into historical relics and promote socialization within the community to encourage the preservation of historical artifacts in Rembitan Village. The method used is to identify historical heritage sites and collaborate with the community to preserve them. Examples of such sites include the Rembitan Ancient Mosque, the traditional house of the Sasak tribe in Sade Hamlet, and the Tomb of Wali Nyatoq. The educational activities and preservation of historical heritage sites have resulted in enthusiastic participation from students and cooperation from the community to introduce and maintain historical places in Rembitan village. From the community to introduce and maintain historical places in Rembitan village. Keywords: Community Education; Historical Remembrance; Central Lombok.